Evaluation of a Novel FKS1 R1354H Mutation Associated with Caspofungin Resistance in Candida auris Using the CRISPR-Cas9 System - Maiko Kiyohara; Taiga Miyazaki; Michiyo Okamoto; Tatsuro Hirayama; Koichi Makimura; Hiroji Chibana; Nana Nakada; Yuya Ito; Makoto Sumiyoshi; Nobuyuki Ashizawa; Kazuaki Takeda; Naoki Iwanaga; et al. (Journal of Fungi, 2023)
Outbreaks of invasive infections, with high mortality rates, caused by multidrug-resistant Candida auris have been reported worldwide. Although hotspot mutations in FKS1 are an established cause of echinocandin resistance, the actual contribution of these mutations to echinocandin resistance remains unknown. Here, we sequenced the FKS1 gene of a caspofungin-resistant clinical isolate (clade I) and identified a novel resistance mutation (G4061A inducing R1354H). We applied the clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 system to generate a recovered strain (H1354R) in which only this single nucleotide mutation was reverted to its wild-type sequence. We also generated mutant strains with only the R1354H mutation introduced into C. auris wild-type strains (clade I and II) and analyzed their antifungal susceptibility. Compared to their parental strains, the R1354H mutants exhibited a 4- to 16-fold increase in caspofungin minimum inhibitory concentration (MIC) while the H1354R reverted strain exhibited a 4-fold decrease in caspofungin MIC. In a mouse model of disseminated candidiasis, the in vivo therapeutic effect of caspofungin was more closely related to the FKS1 R1354H mutation and the virulence of the strain than its in vitro MIC. The CRISPR-Cas9 system could thus aid in elucidating the mechanism underlying drug resistance in C. auris.